2016
DOI: 10.1016/j.jid.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Proliferative Function of Mitochondrial Sirtuin Deacetylase SIRT3 in Human Melanoma

Abstract: Melanoma, the most aggressive forms of skin cancer, is often fatal if not treated early. Therefore, novel target-based strategies are required to combat this neoplasm. The objective of this study was to determine the role and functional significance of the mitochondrial sirtuin SIRT3 in melanoma. We found that compared to normal primary and immortalized human melanocytes, SIRT3 is significantly overexpressed in multiple human melanoma cells at mRNA and protein levels. Further, employing human tissue microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 39 publications
5
62
1
Order By: Relevance
“…However, the relevance of cytoplasmic SIRT3 needs to be carefully investigated in future studies. In a very recent study from our laboratory, we found that SIRT3 is overexpressed in human melanoma cells and clinical melanoma tissues (58). Further, a short hairpin RNA (shRNA)-mediated knockdown of SIRT3 was found to impart significant anti-proliferative effects in multiple human melanoma cell lines (58).…”
Section: Mitochondrial Sirts and Their Molecular Targets: Relevance Tmentioning
confidence: 95%
See 3 more Smart Citations
“…However, the relevance of cytoplasmic SIRT3 needs to be carefully investigated in future studies. In a very recent study from our laboratory, we found that SIRT3 is overexpressed in human melanoma cells and clinical melanoma tissues (58). Further, a short hairpin RNA (shRNA)-mediated knockdown of SIRT3 was found to impart significant anti-proliferative effects in multiple human melanoma cell lines (58).…”
Section: Mitochondrial Sirts and Their Molecular Targets: Relevance Tmentioning
confidence: 95%
“…In a very recent study from our laboratory, we found that SIRT3 is overexpressed in human melanoma cells and clinical melanoma tissues (58). Further, a short hairpin RNA (shRNA)-mediated knockdown of SIRT3 was found to impart significant anti-proliferative effects in multiple human melanoma cell lines (58). Conversely, forced exogenous overexpression of SIRT3 promoted enhanced proliferative potential of Hs294T melanoma cells and normal immortalized Mel-ST melanocytes (58).…”
Section: Mitochondrial Sirts and Their Molecular Targets: Relevance Tmentioning
confidence: 95%
See 2 more Smart Citations
“…Oncogenic properties of SIRT3 are attributed to its actions in stimulation of proliferation, resistance to oxidative stress, and suppression of apoptosis. SIRT3 could play an oncogenic role in a spectrum of cancers including oral squamous cell carcinoma [58], breast cancer [59], esophageal cancer [60], gastric cancer [61], colorectal cancer [62], and melanoma cell lines [63].…”
Section: Changes In Sirtuin 3 Expression In Carcinogenesismentioning
confidence: 99%